2018
DOI: 10.1007/s11661-018-4638-8
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Evolution and Refinement During Liquid–Liquid Decomposition of Zn-6 Wt Pct Bi Immiscible Alloy Under High Static Magnetic Fields

Abstract: In situ solidification experiments on Zn-6 wt pct Bi immiscible alloys were conducted to investigate the droplet evolution under high static magnetic fields (HSMFs). The results showed that a microstructure with extremely fine Bi-rich particles distributed in the matrix can be obtained under an HSMF of 29 T. The average diameter of the Bi-rich phase decreased with the increasing magnetic flux density. Stokes sedimentation disappeared when the HSMF was larger than 18 T. Starting at an HSMF of 18 T, Bi-rich drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Thus, a non-isothermal interface and a J TE will form between the dendrite and the liquid melt surrounding it (the yellow closed circle in Figure 5d). Previous research [51] discovered that a thermoelectric magnetic force (TEMF), created by the interaction of the J TE and an external ASMF, can induce macroscopic unidirectional thermoelectric magnetic convection (TEMC), which would inevitably alter the heat transfer characteristics at the solid-liquid interface. Due to the interaction between J TEX (the x-component of J TE , yellow arrows) and the external ASMF, a macroscopic unidirectional TEMC is also presented in this study, as shown in Figure 5e (the top view of the metal pool).…”
Section: Shallower Metal Pool and Mechanismsmentioning
confidence: 99%
“…Thus, a non-isothermal interface and a J TE will form between the dendrite and the liquid melt surrounding it (the yellow closed circle in Figure 5d). Previous research [51] discovered that a thermoelectric magnetic force (TEMF), created by the interaction of the J TE and an external ASMF, can induce macroscopic unidirectional thermoelectric magnetic convection (TEMC), which would inevitably alter the heat transfer characteristics at the solid-liquid interface. Due to the interaction between J TEX (the x-component of J TE , yellow arrows) and the external ASMF, a macroscopic unidirectional TEMC is also presented in this study, as shown in Figure 5e (the top view of the metal pool).…”
Section: Shallower Metal Pool and Mechanismsmentioning
confidence: 99%
“…Immiscible alloys exhibit a specific type of phase diagram characterized by a miscibility gap in the liquid state [1][2][3][4]. When cooling into the miscible gap, decomposition will happen, a homogeneous single-phase liquid separates into two liquids that are immiscible with each other and will form distinct phases [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…18 They are especially suitable for the manufacturing of either in situ particle composite materials or composite materials with a core/shell structure and thus have a strong industry application background. 913 For instance, Al-Bi alloy can be used as the advanced bearings if the soft Bi phase disperses uniformly in a comparatively hard Al-based matrix, 14,15 and Cu-Fe and Cu-Cr alloys are high-strength, high-electrical-conductivity materials. 1619 However, these alloys have an essential drawback, in that the miscibility gap poses problems during solidification.…”
Section: Introductionmentioning
confidence: 99%